{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# key4fa02 - COT3100C-01 Fall 2002 S Lang Solution Keys to...

This preview shows pages 1–2. Sign up to view the full content.

COT3100C-01, Fall 2002 S. Lang Solution Keys to Assignment #4 (40 pts.) 10/24/2002 Use induction to prove each of the following questions, and be sure to mark clearly when and where the induction hypothesis is applied in each question: 1. (10 pts.) . 16 5 ) 1 4 ( 5 5 , 1 integer for that Prove 1 1 + - = + = n j n n n j j Answer : We use induction on n 1. (Basis Step) Consider n = 1. In this case, the LHS = . 5 5 1 5 1 1 1 = = = j j j The RHS = . 5 16 80 16 5 3 25 16 5 ) 1 4 ( 5 1 1 = = + = + - + Thus, LHS = RHS, so the Basis Step is proved (Induction Hypothesis) Consider n = k . Suppose 16 5 ) 1 4 ( 5 5 1 1 + - = + = k j k k j j for some k 1. (Induction Step) Consider n = k +1. We need to prove (1) - - - 16 5 ) 3 4 ( 5 16 5 ) 1 ) 1 ( 4 ( 5 5 2 1 1 1 1 + + = + - + = + + + + = k k j k k k j j (1). of RHS 16 5 ) 3 4 ( 5 16 5 ) 3 4 ( 5 5 16 5 ) 15 20 ( 5 16 5 ) 16 16 1 4 ( 5 16 5 ) 1 ( 16 5 ) 1 4 ( 5 Hypothesis Induction by the , 5 ) 1 ( 16 5 ) 1 4 ( 5 summation of definition by the , 5 ) 1 ( 5 (1) of LHS that the Note 2 1 1 1 k 1 1 k 1 1 k 1 1 = + + = + + = + + = + + + - = + + + - = + + + - = + + = + + + + + + + + + = k k k k k k k k k k j k k k k k k k j j Thus, the Induction Step is proved.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 3

key4fa02 - COT3100C-01 Fall 2002 S Lang Solution Keys to...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online